Weathering the Storm: The Impact of the East Asian Crisis on Farm Households in Indonesia and Thailand - Bresciani, Fabrizio; Feder, Gershon; Gilligan, Daniel O.; Jacoby, Hanan; Onchan, Tongroj; Quizon, Jaime B. (Oxford University Press, 2002)
This article assesses the impact of the East Asian financial crisis on farm households in two of the region's most affected countries. Indonesia and Thailand, using detailed household-level survey data collected before and after the crisis began. Although the nature of the shocks in the two countries were similar, the impact on farmers' income (particularly on distribution) was quite different. In Thailand, poor farmers bore the brunt of the crisis, in part because of their greater reliance on the urban economy, than did poor farmers in Indonesia. Urban-rural links are much weaker in Indonesia. Farmers in both countries, particularly those specializing in export crops, benefited from the currency devaluation. Although there is some evidence that the productivity of the smallest landholders declined over the period in question, it is difficult to attribute this directly to the financial crisis. At least in Thailand, a rural credit crunch does not seem to have materialized.